Genesis of carbonate till in the lee sides of Precambrian Shield uplands, Hemlo area, Ontario - Hicock, Stephen R. (Canadian Journal of Earth Sciences, 1987)
Near Hemlo, Ontario, highly calcareous till is confined to areas located downglacier from Precambrian uplands, at least 150 km from the Paleozoic–Precambrian boundary. It comprises subglacial meltout till between lodgment tills, and the calcareous package overlies noncalcareous basal till (not studied) and underlies noncalcareous supraglacial meltout till. The tills can be distinguished by textural, carbonate, and clast compositions. Glaciotectonic deformations, stone fabrics and striae, and stone provenance from the tills, as well as erosional and depositional landforms, indicate that ice advanced to the south–southwest across bedrock contacts and over Precambrian uplands.Deposition of all five tills can be explained with one glacial event. As the Late Wisconsinan margin of the Laurentide ice sheet advanced against uplands about 20 km northeast of Hemlo it experienced compressive flow while depositing the non calcareous basal till. Upshearing of stoss-side local debris high into the ice also occurred as englacial ice overrode the slowed basal zone. Once over the upland, englacial ice assumed extending flow, and downshearing of distal debris, which was deposited as calcareous lodgment till on the lee sides of uplands. After the glacial maximum, the glacier ceased internal movement and subglacial meltout till was laid down. A late reactivation of the ice deposited the upper lodgment till and final stagnation formed the supraglacial meltout till.